Drowning prevention: turning the tide on a leading killer - David R Meddings, MD; Justin-Paul Scarr, MBA; Kelly Larson, MPH; James Vaughan; Etienne G Krug, MD (Elsevier, 2021)
Summary: Drowning is a leading killer, particularly of children and young adults, yet has been greatly neglected. Despite accounting for a higher number of deaths than many other substantial public health issues, drowning has not benefitted from the targeted attention it requires, which is particularly tragic because low cost and effective drowning prevention interventions exist. Therefore, the recent UN General Assembly's adoption of a resolution on global drowning prevention is a historic first, and offers an exciting opportunity by providing a comprehensive framework and a practical roadmap that a range of actors and sectors, including governments, can follow to address the challenge of drowning prevention.